Introducing and evaluating elements of alignment, congruence and feedback to a MSc programme - Brandt Sørensen, Jane (Improving University Science Teaching and Learning, 2023)
It is well-established that congruence and constructive alignment of teaching to university students is an appropriate tool to enhance engagement, motivation, learning processes and outcomes (Hounsell et al., 2005). Furthermore, formative feedback and self-regulated learning can be a means for the students to take control of their own learning (Nicol & Macfarlane Dick, 2006). Using the case of the course ‘Global Health and Diseases’, this final project will explore how the introduction of congruence and constructive alignment as well as feedback can influence students’ perception of learning.